USULAN PERBAIKAN KUALITAS PELAYANAN DI UNIT PELAKSANA PTSP KOTA ADMINISTRASI JAKARTA BARAT MENGGUNAKAN METODE FUZZY-SERVQUAL DAN QFD - Dwi Rahmawati (Operations Excellence: Journal of Applied Industrial Engineering, 2017)
One Door Integrated ServiceUnit (PTSP) was established to improve the quality of public service delivery and the investment climate in the regions of Indonesia, particularly in the field of licensing services. The purpose of this study is to identify the variables that affect the quality of licensing government service and provide recommendations for corrective action. In this research, the integration of Fuzzy-Service Quality and QFD (Quality Function Deployment)method is one of TQM quantitative tools and techniques that can be used to translate customer requirements in Voice of customer (VOC) with specification in the appropriate technical or service requirement. The use of questionnaires, based on servqual dimension i.e. tangibles,r eliability, responsiveness, assurance and empathy contains 27 statements as attributes of service, conducted to know the voice of customer to 135 respondents i.e. the citizens who use licensing service in UPPTSP West Jakarta administration. The results showed that there are 11 service attribute priorities that need to be improved and 14 technicalr esponses to answer the needs of these consumers.